2023
DOI: 10.3390/healthcare11010146
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Methods Sequential Explanatory Study of the Factors That Impact Nurses’ Perspectives toward Nurse Practitioners’ Roles in Saudi Arabia

Abstract: Nurse practitioners’ roles need to be clearly defined in Saudi Arabia. Therefore, we aimed to explore potential factors that impact nurses’ perspectives toward nurse practitioners’ roles and whether they are interested in becoming nurse practitioners. A mixed-methods study design was employed using a questionnaire and focus groups. The survey was sent to nurses working at a public hospital in the Riyadh region. Participants (N = 77) reported that having more nurse practitioners would improve quality of care an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…Nevertheless, participants identifed several patientrelated, organizational, and professional positive impacts of APN in Saudi Arabia. Similar fndings were reported in recent studies in Saudi Arabia [25][26][27] and worldwide [28][29][30][31].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, participants identifed several patientrelated, organizational, and professional positive impacts of APN in Saudi Arabia. Similar fndings were reported in recent studies in Saudi Arabia [25][26][27] and worldwide [28][29][30][31].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, participants indicated that APN may face resistance from physicians, nurses, and patients, which was consistent with previous studies [34]. However, recent studies revealed that physicians [12] and nurses [26,27] in Saudi Arabia supported the implementation of APN. To the best of our knowledge, no studies have explored the patients' experiences with the care provided by APNs.…”
Section: Discussionsupporting
confidence: 86%
“…There is a lack of consensus on the core competencies and delineation of APN roles and activities globally (Heale & Rieck Buckley, 2015). Similarly, in Saudi Arabia, there is confusion and ambiguity about the roles and practice patterns of nurses, including advanced practice nurses, and about the usage of the term APN (Hibbert et al, 2017; Kerari et al, 2023).…”
Section: Discussionmentioning
confidence: 99%